A complex variable boundary element method for axisymmetric heat conduction in a nonhomogeneous solid - Ang, Whye Teong (2011)
A complex variable boundary element method is proposed for solving numerically the axisymmetric steady-state problem of heat conduction in a nonhomogeneous isotropic solid. To assess the validity and the accuracy of the method, it is applied to solve specific cases of the problem. The numerical solutions obtained agree well with known solutions.